1999
DOI: 10.1021/jp9921295
|View full text |Cite
|
Sign up to set email alerts
|

Potential Energy Surfaces for LiH2 and Photochemical Reactions Li*+ H2 ↔ LiH + H

Abstract: Potential energy surfaces for the Li*+ H2 → LiH + H and the reverse reactions are calculated using ab initio methods. Extensive configuration interactions have been done for a large number of collinear, C 2 v , and C s geometrical forms using a large basis set to describe the 2s−3d atomic states of the lithium atom and the neutral and anionic hydrogen molecule. The Li(3s) channel has a small activation barrier and leads to a stable intermediate, 4 2A‘ (LiH2)*, but a diabatic coupling between the 3 and 4 2A‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
72
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 35 publications
12
72
1
Order By: Relevance
“…they also reported that there is a small barrier with the height of about 0.04 eV. After a short time, Lee et al 4 reported a new ground state PES which shows a downhill descending shape from the initial state H+HLi to the final state H 2 +Li, and they found that 1 2 A' intermediate plays an important role in the reaction process. Dunne et al 5 derived an analytical potential energy surface named DMJ PES by fitting a many-body potential to energies obtained from high quality ab initio (CI) calculations and carried out the reaction cross sections for reaction H+HLi → H 2 +Li at various collision energies and selected rotational states.…”
Section: 2mentioning
confidence: 93%
See 1 more Smart Citation
“…they also reported that there is a small barrier with the height of about 0.04 eV. After a short time, Lee et al 4 reported a new ground state PES which shows a downhill descending shape from the initial state H+HLi to the final state H 2 +Li, and they found that 1 2 A' intermediate plays an important role in the reaction process. Dunne et al 5 derived an analytical potential energy surface named DMJ PES by fitting a many-body potential to energies obtained from high quality ab initio (CI) calculations and carried out the reaction cross sections for reaction H+HLi → H 2 +Li at various collision energies and selected rotational states.…”
Section: 2mentioning
confidence: 93%
“…[3][4][5][6][7][8][9][10][11][12][13] The pioneer work can be traced to Clarke et al, 3 where they firstly calculated the adiabatic LiH 2 potential energy surface using the spin-coupled valence bond (SCVB) non-orthogonal configuration interaction (CI) method, and found that cold LiH molecules can be depleted by reactive encounters with H atom at low collision energy. they also reported that there is a small barrier with the height of about 0.04 eV.…”
Section: 2mentioning
confidence: 99%
“…[11][12][13][14] The LiH 2 chemical system has been the subject of a large number of studies on its potential energy surfaces (PESs), on the sub-reactive or reactive collision dynamics during the past decade. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] The ground state potential energy surface (PES) of LiH 2 system for the collinear arrangement was initially constructed by Clarke et al 16 and also for the threedimensional configurations by Dunne, Murrell, and Jemmer (DMJ PES). 18 Clarke and coworkers 16 have calculated the initial state selected reaction probabilities for the depletion and formation reaction of LiH by the quasi-classical trajectory (QCT) and the quantum time-dependent wave packet method for the special collinear arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the reaction mechanism appears similar to the hydrogenation reaction of the alkali atom studied by our group. 15,16 In summary, the end-on geometry is the most favourable for the reaction to take place. It is at the same time closer to the reactant and the product than the C 2v intermediate isomer.…”
Section: Resultsmentioning
confidence: 99%